2014
DOI: 10.1038/sc.2014.189
|View full text |Cite
|
Sign up to set email alerts
|

Does regular standing improve bowel function in people with spinal cord injury? A randomised crossover trial

Abstract: Study Design: A randomised crossover trial. Objectives: To determine the effects of a 6-week standing programme on bowel function in people with spinal cord injury. Setting: Community, Australia and the United Kingdom. Methods: Twenty community-dwelling people with motor complete spinal cord injury above T8 participated in a 16-week trial. The trial consisted of a 6-week stand phase and a 6-week no-stand phase separated by a 4-week washout period. Participants were randomised to one of two treatment sequences.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 22 publications
0
12
0
1
Order By: Relevance
“…ROBO-FES increased leg strength by 1.97 ± 0.88 points, ROBO by 1.50 ± 0.85 more than controls (1.03 ± 0.61, P < 0.05). Cerebral blood flow volume increased in ROBO groups more than controls (P < 0.05) Kwok 2015 [ 59 ] Randomized Crossover Moderate quality (moderate risk) 17 Chronic SCI Tilt-table, as upright as possible 30 mins day 5 × wk × 6 weeks (150 mins/week) No difference in time to first stool or time for bowel care routine. 8/17 reported improved bowel function including decreased abdominal distention.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…ROBO-FES increased leg strength by 1.97 ± 0.88 points, ROBO by 1.50 ± 0.85 more than controls (1.03 ± 0.61, P < 0.05). Cerebral blood flow volume increased in ROBO groups more than controls (P < 0.05) Kwok 2015 [ 59 ] Randomized Crossover Moderate quality (moderate risk) 17 Chronic SCI Tilt-table, as upright as possible 30 mins day 5 × wk × 6 weeks (150 mins/week) No difference in time to first stool or time for bowel care routine. 8/17 reported improved bowel function including decreased abdominal distention.…”
Section: Resultsmentioning
confidence: 99%
“…Other evidence for impact of standing on bowel and bladder function has only been studied with the SCI population. A randomized trial [ 59 ] found no change in objective measures of bowel function although 8/17 participants reported improvement. Survey and single case study evidence suggests that use of a standing device can improve bowel function [ 20 , 22 , 44 , 54 ] and Dunn [ 38 ] found a correlation between this outcome and use of a standing device daily, for more than 30 min per bout.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…O tempo necessário para defecação é um dado clinicamente relevante pois está fortemente associado com o impacto que o manejo intestinal traz para QV das pessoas com LM (KROGH et al, 2009;BURNS et al, 2015). Mesmo com vários estudos realizados sobre a avaliação do manejo intestinal ou avaliação de efeitos terapêuticos sobre a função intestinal de pessoas com LM, demonstrando que as mesmas podem necessitar de um tempo acima de 30 minutos para defecação, podendo chegar a duas horas (ENGKASAN;SUDIN, 2013;HANSEN et al, 2015;KWOK et al, 2015), a maioria dos participantes da presente pesquisa, cerca de 90%, relataram necessitar de até 30 minutos para os cuidados intestinais. Nesse sentido, os dados encontrados corroboram com outro estudo que concluiu que as pessoas com LM devem ser capazes de completar seus cuidados intestinais dentro de 45 minutos no máximo, e caso esse tempo ultrapasse mais de uma hora que então seja considerado um caso de disfunção intestinal (ENGKASAN; SUDIN, 2013).…”
Section: Critérios De Exclusãounclassified
“…16 The NBD score has been translated into several languages and recently used in several research on symptoms, pathophysiology and management of NBD in SCI. [17][18][19][20][21][22][23][24] Finally, NBD score has been added to the International SCI Bowel Function Basic Data Set (Version 2.0) that is a simple, standardized tool developed for the collection and reporting of a minimal amount of information on bowel function in daily practice and research. 25 However, the studies investigating the validity and reliability of NBD score are still limited, and there is no study that showed the sensitivity to change of NBD score.…”
Section: Introductionmentioning
confidence: 99%